The effect of interactional classroom peer work on the treatment of mistakes in students’ academic essays - Khuwaileh, Abdullah A. (The ESPecialist, 2012)
There is a wide body of theoretical and practical research on the importance of the writing skill in teaching and learning Academic English. The focus of the vast majority of this research has been on error analysis, testing, needs and evaluation of writing. However, the purpose of this study was to measure the effect of classroom peer work on the development of students’ ability of academic essay writing, a topic which is a relatively neglected area. By focusing on the treatment of writing mistakes, the study gives more attention to the students’ role in developing their ability to identify their errors and to treat them properly through a process of three stages carried out under the supervision of their teacher (the researcher). Therefore, the study aims at reducing if not eliminating these mistakes through classroom interaction. After establishing a control group and an experimental one, we found that maximizing the students’ role in learning essay writing initiated very positive results on their ability to write essays free of mistakes and even to speak to an audience. The three stages interactional process of essay writing was a practice in Jordan University of Science and Technology (hereafter JUST) where the study was carried out. But it can be applied in other English language teaching situations similar to that of JUST. Therefore, the process is highly recommended in the case of teaching paragraph writing, term papers and skill integration not only for Arab learners of English, but also for other speakers of English who have different first languages.